2011
DOI: 10.1503/cmaj.100467
|View full text |Cite
|
Sign up to set email alerts
|

Drug formulations that require less than 0.1 mL of stock solution to prepare doses for infants and children

Abstract: Research

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 15 publications
(8 reference statements)
0
16
2
2
Order By: Relevance
“…Isaac et al 35 found that 25% of patients on paediatric intensive care units were prescribed a medicine that required a small volume measurement of ≤0.2 mL, with the intravenous route accounting for 80% of the drug delivery methods. Uppal et al 14 provide further support, stating that 7.4% of intravenous doses require preparation with <0.1 mL of stock solution. It was concluded that this is necessary for the paediatric use of a wide range of narcotics and immunosuppressants in Canada14 with captopril, morphine, furosemide and ranitidine the most commonly found in the UK 35…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Isaac et al 35 found that 25% of patients on paediatric intensive care units were prescribed a medicine that required a small volume measurement of ≤0.2 mL, with the intravenous route accounting for 80% of the drug delivery methods. Uppal et al 14 provide further support, stating that 7.4% of intravenous doses require preparation with <0.1 mL of stock solution. It was concluded that this is necessary for the paediatric use of a wide range of narcotics and immunosuppressants in Canada14 with captopril, morphine, furosemide and ranitidine the most commonly found in the UK 35…”
Section: Resultsmentioning
confidence: 97%
“…Uppal et al 14 provide further support, stating that 7.4% of intravenous doses require preparation with <0.1 mL of stock solution. It was concluded that this is necessary for the paediatric use of a wide range of narcotics and immunosuppressants in Canada14 with captopril, morphine, furosemide and ranitidine the most commonly found in the UK 35…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A retrospective study performed by Uppal and colleagues examined medications that had commercially available parenteral formulations listed in the Hospital for Sick Children formulary, and it was found that 22 % of medications used in neonates had one or more indications that required less than 0.1 mL of stock solution [68]. In an additional clinical observational study, these investigators found that over 7 % of the doses administered to patients admitted to their pediatric intensive care unit over a 1-year period were prepared from less than 0.1 mL of stock solution [68]. While concentration data were not available for patients treated with these drugs, it is likely that there would have been a large variability resulting from the imprecise dosing often seen with doses prepared from less than 0.1 mL of stock solution.…”
Section: Intravenousmentioning
confidence: 99%
“…There is a risk that the dose delivered will be inaccurate and that medication errors may occur when calculating and preparing doses 4. There is little information about the extent of manipulation in paediatric practice, the accuracy with which dosage forms can be manipulated or the drugs commonly involved 5 6…”
Section: Introductionmentioning
confidence: 99%